Website Based Ticket Ordering Application Design Using Laravel Framework (Bedegung Waterfall Tour, Muara Enim Regency) - Gunawan, Wawan; Liana, Lia Nur (LPPM Institut Teknologi Telkom Purwokerto, 2025)
Bedegung Waterfall is a well-known natural tourism destination located in Bedegung Village, Muara Enim Regency, offering beautiful scenery and a prominent waterfall. Despite its popularity, the ticket booking process is still conducted manually, resulting in long queues, slow transactions, service delays, and traffic congestion around the tourist area, which reduces visitor comfort and management efficiency. To address these issues, this study proposes developing a web-based ticket-booking application to streamline transactions and enhance tourism service quality. The system was designed and developed using the Extreme Programming (XP) software development method to ensure flexibility, rapid development, and effective collaboration. The application was implemented using the Laravel framework, PHP as the programming language, and MySQL as the database management system, due to its reliability in handling large volumes of data. System design was supported by Flowcharts, Use Case Diagrams, Class Diagrams, Activity Diagrams, and Entity-Relationship Diagrams (ERDs) to clearly describe system workflows and data relationships. The objective of this research is to design, implement, and evaluate a web-based ticket booking system that improves transaction efficiency, reduces queues, and enhances visitor convenience. The system supports three user roles: Super Admin, Tourist Staff, and Member, each with distinct access rights and functionalities. System testing was conducted using the Black-Box Testing method to evaluate functional suitability against user requirements. A total of 37 testing scenarios were executed across all user roles, and the results showed that all system functions operated as expected, achieving a 100% testing success rate, indicating that the developed application is effective and feasible for implementation at Bedegung Waterfall.